The Importance of Hospital Image, Service Trust Level, and Physiotherapy Service Satisfaction on Patient Loyalty: A Case Study in a Type D Private Hospital - Gabrina Selvi Yanuarista; Septo Pawelas Arso; Sri Winarni (Journal of Public Health Sciences, 2026)
Patient loyalty is essential for sustaining physiotherapy services, where prolonged treatment and discomfort often lead to high drop-out rates. This mixed-methods observational study examined how hospital image and patient trust shape satisfaction and loyalty among physiotherapy outpatients at KS Hospital between March and May 2025. A total of 160 outpatients were recruited through accidental sampling and completed a structured questionnaire, analyzed using partial least squares structural equation modeling (PLS-SEM). Qualitative data were gathered through in-depth interviews with a service manager, a specialist, and patients, triangulated to validate and enrich the quantitative findings. Hospital image significantly predicted satisfaction (β = .544, p < .001) and indirectly influenced loyalty through satisfaction (β = .202, p < .001). Patient trust showed both direct (β = .274, p < .001) and satisfaction-mediated (β = .294, p < .001) effects on loyalty. Satisfaction was the central mediating variable, explaining 70% of the variance in loyalty (R² = .695), with word-of-mouth emerging as its strongest indicator. Interview findings reinforced that service uniqueness and facility quality strengthen image and trust, which in turn foster satisfaction and encourage patients to return. These results underscore satisfaction's pivotal role in translating hospital image and trust into patient loyalty. Hospital management should prioritize improving service responsiveness and distinctiveness while ensuring equitable, empathetic care to strengthen long-term patient commitment to physiotherapy services. As a result, patient visit numbers can be maintained or even improved.